Evaluating immediate and long‐term impacts of qualitative group model building workshops on participants' mental models. (12th February 2014) - Scott, Rodney J.; Cavana, Robert Y.; Cameron, Donald
Abstract Group model building literature reports that participation causes mental model refinement and alignment, but no previous study appears to have examined whether these changes are enduring. This paper reports on a case study involving four groups using group model building tools that were evaluated immediately before, immediately after, and 12 months following a 3‐hour workshop. Each workshop used qualitative group model building to plan strategy implementation initiatives in a government department. A change of circumstances (merger and restructure) meant that the workshop conclusions were not implemented, providing a research opportunity to measure the enduring effects of group model building workshops. Statistical comparison of written responses suggests that participants' views on the workshop topic changed and became more alike through the workshop process, and that these changes were enduring even in the relative absence of reinforcing activities. Copyright © 2014 System Dynamics Society